Orbital Lymphoma Masquerading as Orbital Cellulitis - B. D. Chaurasiya; Ganesh Agrawal; Santosh Chaudhary; Sangeeta Shah; Anju Pradhan; Poonam Lavaju (Case Reports in Ophthalmological Medicine)
Background. Orbital lymphomas are primarily non-Hodgkin type and can originate from the eyelids, extraocular muscles, soft tissue orbital adnexa, conjunctiva, or lacrimal glands. Orbital malignancies often represent a diagnostic dilemma for clinicians given their varying and atypical presentations. Objective. To report a case of orbital lymphoma mimicking orbital cellulitis. Case. A 66-year-old male patient presented with sudden onset of painful proptosis with visual impairment in the left eye for 15 days. On ocular examination, best-corrected visual acuity was 6/12 in the right eye and 2/60 in the left eye, abaxial proptosis with hypertropia, swollen and erythematous eyelids, restricted extraocular movement in all cardinal position of gaze, conjunctival congestion with chemosis and tortuous vessels, sluggish pupillary reaction, and chorioretinal folds in the inferior quadrants. The case was diagnosed as left eye orbital cellulitis, and the patient was treated with broad-spectrum intravenous antibiotics and oral steroids. No clinically discernible response was noted despite 7 days of antibiotics and steroids. Contrast-enhanced computed tomography (CECT) orbit showed features suggestive of orbital lymphoma involving the ipsilateral maxillary and ethmoid sinuses. ENT consultation with diagnostic nasal endoscopy and biopsy was done. Histopathological reports showed features of non-Hodgkin lymphoma. Conclusion. Orbital malignancies masquerading as orbital cellulitis can pose a diagnostic dilemma. A multidisciplinary approach involving ENT consultation, radiological investigation, and pathological sampling can help achieve a timely diagnosis and appropriate management.